Assessing Information System Integration Using Combination of the Readiness and Success Models - A'ang Subiyakto (Bulletin of Electrical Engineering and Informatics, 2018)
Information system integration (ISI) is one of the development concerns for organizations to enhance business competitiveness. However, the implementations still present its failures. Despite the ISI may successful technically; but it still seems to be unsuccessful because of the human and management issues. The issues may relate to the readiness constructs of ISI. This study was aimed to know the status of the readiness and success of ISI and to assess the influential factors of the integration in the sampled institution. About 160 samples were purposely involved by considering their key informant characteristics. The data were analyzed using the partial least squares-structural equation modeling (PLS-SEM) method. The findings revealed only the user satisfaction variable that mediated the positive effects of the readiness variables towards variable of the system integration success. Besides, the findings may practically helpful for stakeholders in the sampled institution, but it may also theoretically useful for researchers in regard to the readiness and success issues of ISI.